Molecular Mechanisms Underlying the Activation of Mammalian Primordial Follicles - Adhikari, Deepak; Liu, Kui (Endocrine reviews, 2009)
In humans and other mammalian species, the pool of resting primordial follicles serves as the source of developing follicles and fertilizable ova for the entire length of female reproductive life. One question that has intrigued biologists is: what are the mechanisms controlling the activation of dormant primordial follicles. Studies from previous decades have laid a solid, but yet incomplete, foundation. In recent years, molecular mechanisms underlying follicular activation have become more evident, mainly through the use of genetically modified mouse models. As hypothesized in the 1990s, the pool of primordial follicles is now known to be maintained in a dormant state by various forms of inhibitory machinery, which are provided by several inhibitory signals and molecules. Several recently reported mutant mouse models have shown that a synergistic and coordinated suppression of follicular activation provided by multiple inhibitory molecules is necessary to preserve the dormant follicular pool. Loss of function of any of the inhibitory molecules for follicular activation, including PTEN (phosphatase and tensin homolog deleted on chromosome 10), Foxo3a, p27, and Foxl2, leads to premature and irreversible activation of the primordial follicle pool. Such global activation of the primordial follicle pool leads to the exhaustion of the resting follicle reserve, resulting in premature ovarian failure in mice. In this review, we summarize both historical and recent results on mammalian primordial follicular activation and focus on the up-to-date knowledge of molecular networks controlling this important physiological event. We believe that information obtained from mutant mouse models may also reflect the molecular machinery responsible for follicular activation in humans. These advances may provide a better understanding of human ovarian physiology and pathophysiology for future clinical applications.